On the taxonomy and distribution of Diamesa gregsoni Edwards, (Diptera: Chironomidae: Diamesinae), with morphological redescription and DNA barcoding of species from the Far East - Semenchenko, Alexander A.; Makarchenko, Eugenyi A. (Zootaxa, 2025)
By analyzing the DNA barcoding data of the Diamesa gregsoni Edwards syntype, we carried out a genetic study of this species from the Far East and made a comparison with DNA barcodes of North American populations. A morphological redescription of the adult male and a description of the pupa and larva are given, and the taxonomy and distribution of the species are clarified in this study. The Bayesian tree revealed two well-supported clades of D. gregsoni from Nearctic and Palaearctic. The average K2P genetic divergence between these clades was 1.67%, which corresponds to intraspecific differences. Overall intraspecific p-distances within 23 DNA barcodes of D. gregsoni were 1.19%. The Automatic Barcode Gap Discovery (ABGD), Assemble Species by Automatic Partitioning (ASAP), and Multi-rate Poisson tree processes (mPTP) approaches for the species delimitation confirmed that Nearctic and Palaearctic DNA barcodes belong to a single molecular taxonomic unit, while general mixed Yule-coalescent (GMYC) delimit the dataset into three different molecular operational taxonomic units (mOTU).